Post-mortem Computed Tomography (PMCT) Imaging Compared to Conventional Autopsy in Establishing Cause of Death in Adults - Yew, Ting Ting; Zahiah, Mohamed; Faridah, Mohd Nor (Faculty of Medicine And Health Sciences, Universiti Putra Malaysia, 2024)
Introduction: The aim of this study was to determine whether the post-mortem computed tomography (PMCT) findings are able to correlate well with the cause of death on conventional autopsy. Materials and methods: From January 2008 until September 2016, total of 60 bodies underwent PMCT scans in the radiology department, fol- lowed by conventional autopsies conducted in the forensic department. The radiological findings were interpreted, which were then correlated with the cause of death based on conventional post-mortem autopsy and/or pathological diagnosis. Results: The PMCT findings correlated well with the conventional autopsies. In 28 cases (46.7%), the cause of death was diagnosable based on PMCT alone, in nine cases (15%) the cause was suggestive but required additional information, and in 23 cases (38.3%) the cause was not diagnosable based on PMCT alone. Diagnosable cases included those involving gunshot wounds, sharp and blunt injuries, and lung infections. Causes that could not be diagnosed through PMCT alone included acute myocardial infarction, burns, asphyxiation, drug intoxication and septicemia. Conclusion: PMCT proves to be a valuable and excellent tool for documenting and illustrating bone frac- tures, abnormal air and fluid accumulation compared to soft tissue injuries, which are better detected in autopsies. However, PMCT alone cannot replace conventional autopsy, which remain the gold standard for establishing the cause of death. Nevertheless, PMCT can serve as useful adjunct in forensic investigations.